Uji empirik strategi struktur modal pecking order pada perusahaan-perusahaan non keuangan lq45 bursa efek indonesia - Adrianto Adrianto; Buddi Wibowo (INOVASI, 2019)
This paper tests the pecking order hypothesis whether it confirms the empirical result on LQ45 firms—which in some senses are having relatively smaller assymmetric information problem than other go public firms in Indonesia. The result shows that financing deficit, profitability, and lagged leverage can significantly determine current shock of long-term debt. R² value changed significantly after the former variable added in to the model, indicating that it is the biggest—but not a single—factor determining net debt issuance. Yet, this variabel has a magnitude of about 0.60, indicating that it doesn’t respond one-on-one with debt. Thus, it appears that the theory has less power in explaning LQ45 firms’ capital decisions